Visualisasi Data Kependudukan Daerah Kabupaten Tangerang Menggunakan Aplikasi Microsoft Power Bi. - Murtiwiyati Murtiwiyati; Dicky Dwi Hermawan; Leli Safitri (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Tangerang Regency is a district located in Banten Province, Indonesia. Tangerang Regency is divided into 29 sub-districts, 28 sub-districts and 246 villages. The Tangerang Regency Opendata Portal is a DKAN-based platform, which is a community-based, free and open-source open data platform that provides freedom for organizations and individuals to publish and consume structured information. The Tangerang Regency opendata portal provides datasets that are useful for local communities to find out various types of information such as economic, social, educational, health, population and so on. So that this data can be processed into valuable information, tools are needed to visualize these data so that they can display information about population datasets, these tools include Business Intelligence (BI) software. This research aims to provide a clear picture or visualization of population data for the Tangerang Regency area from 2019 to 2021. This research was conducted using the Microsoft Power BI application with stages of data collection, data entry, data modeling and data visualization. The results of this research are in the form of a dashboard/summary report and detailed reports regarding population data for Tangerang Regency.